Электромагнитное поле кабеля с двухслойным экраном - Боев, Вячеслав Михайлович (НТУ "ХПИ", 2014)
Приведен расчет электромагнитного поля коаксиального кабеля с двухслойным экраном. Для описания удельной электропроводности и магнитной проницаемости использованы разрывные функции, что дало возможности решать задачу для всего пространства, содержащего кабель, как односвязной области.

The paper presents electromagnetic field calculations for a coaxial cable with a double-layer shield. To describe the conductivity and permeability, discontinuous functions are applied, which makes it possible to solve the problem regarding the whole space containing the cable as a simply connected domain.
Electromagnetic field of a cable with a two-layer shield
Keywords: коаксиальный кабель; электропроводность; магнитная проницаемость; тороидальная область; electromagnetic field; coaxial cables; discontinuous functions